Economic analysis between foreign bias, home bias, economic growth and return correlation - Lee, Pei Ling (2017)
Utilizing 650 country-pairs from the years 2001 through 2014, this research examines whether social trust influences foreign equity bias. Trust, the fundamental component in social capital, is neglected considering the high risks and uncertainty associated with foreign investment.The findings offer new evidence on the linkage between trust and foreign bias. Foreign investment decision depends largely on generalized trust put in other country. Evidently, less trusting society tends to have stronger bias towards foreign countries. However, no evidence provided that individualistic countries show greater preference towards foreign equity. Other traditional financial barriers such as home bias, geographical distance, financial development, common membership in the European Economic and Monetary Union are significant in explaining foreign bias based on the random-effectstobit model. The results are robust despite the use of different estimation methods and procedures.Additionally, understanding the development of home bias is pivotal to have a better grasp of global financial market integration. The second research objective is to investigate the impact of home bias on economic growth by utilizing dynamic panel estimation technique for a sample of 25 countries. Home bias, which is the tendency of over-investing in domestic stock bourse, is proposed to be the proxy of advanced financial integration. Declining home bias is found to hasten the pace of economic development. In other respects, countries with higher labor growth, higher trade openness, and lower exchange rate volatility enjoy higher growth rates. The last objective is to test the effect of portfolio concentration index on market correlation. The relationship between stock market linkages and portfolio concentration is investigated in order not only to reap diversification benefits but also for better understanding the vulnerability a country is subjected to during a global financial crisis. The empirical findings demonstrate the average portfolio concentrations significantly differing between crisis and non-crisis period in their stock market correlations. Portfolio concentration index, real interest rate differential, industrial production growth differential, and stock market size differential are statistically significant in influencing correlation in stock returnsby employing the fixed effect model for a sample of 25 investing and 27 investee countries from 2001 to 2014.